EDUKASI GIZI SEIMBANG SEBAGAI PERISAI PENULARAN COVID-19 PADA KADER POSYANDU BINA SEJAHTERA DAN POSYANDU TULIP - Firdaus Alghifari Atmadja, Taufik; Sulistyaningsih, Dwi; Rifatul Mahmudah, Ifa (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2020)
The addition of positive confirmed cases of COVID-19 in Indonesia continues to occur. Ciamis Regency, which is geographically far from the center of the spread of COVID-19 in Indonesia, cannot be separated from the target of the spread. One of the efforts to prevent virus transmission is by increasing the immune system through balanced nutritional intake. Based on the results of the situation analysis in the Muktisari Village area, information was obtained that the community did not understand the relationship between balanced nutrition and the immune system. The habit of consuming foods with unbalanced nutrition, not paying attention to food safety in processing, and not implementing clean and healthy living habits are problems that must be resolved. Providing education to Posyandu cadres who act as mediators of health information services in the community is expected to be the first step in solving problems. Balanced nutrition education consists of material presentation using power point media and booklet media as well as cooking demonstrations. The positive response of participants to educational activities can be seen from the activeness of the participants, both during the discussion session and during the cooking demonstration. Based on the results of pre-test and post-test data processing, the n-gain value obtained is 0.2. This shows that there is an increase in the understanding of Posyandu cadres before and after the provision of balanced nutrition education